Two new Oxalis (Oxalidaceae) species from the Richtersveld National Park, South Africa - Dreyer, Léanne L.; Roets, Francois; Oberlander, Kenneth C. (Phytotaxa, 2013)
Two new Oxalis species from the Richtersveld National Park (South Africa) are described and typified. Both species show strong morphological resemblance to members of the South African Oxalis section Cernuae. Oxalis nivea sp. nov. closely resembles the well-known weed O. pes-caprae, but it bears white flowers, and has a very restricted distribution range north of the northernmost known locality of O. pes-caprae. Oxalis rosettifolia sp. nov. is distinguished from all other species by a combination of a flat basal rosette of leaves, terete petioles, flask-shaped floral tubes and at least some enlarged, spathulate bracts at the terminal articulation of the peduncle. Phylogenetic analyses based on nuclear ITS and plastid trnSG data confirmed the placement of both of these species within a clade containing O. pes-caprae. The exact placement of these two species differs between ITS- and trnSG-based trees, but both analyses confirm a close relationship between the two new species and O. copiosa and O. cf. haedulipes.